Ekstraksi Pektin dari Kulit Jeruk dan Kulit Pisang sebagai Biosorben pada Proses Adsorpsi Logam Berat Fe - Widya Putri Rahayu; Indah Wulan Harisma; Yanna Syamsuddin; Sofyana Sofyana; Sri Mulyati (Fakultas Teknik, 2021)
One of the alternatives in the treatment of waste containing heavy metals is the use of natural materials as adsorbents, which is known as the biosorption process Pectin is one of the components found in plant cell wall compounds which contain many active groups that plays a key role in the biosorption process which can be used as biosorbents. In this research, the raw materials for pectin resources were orange peel and banana peel. The effectiveness of pectin for both ingredients will be analyzed on the basis of 2 variables, namely the length of contact time (60, 90, 120, and 150 minutes) and the mass of pectin used (20, 30, 40, and 50 mg). The pectin of orange and banana peel was proven by Fourier Transform Infrared (FTIR) analysis shown by C=O functional group of aldehyde and carboxylic acid compounds. The results of this study indicated that the optimum condition was 150 minutes contact with the addition of 50 mg pectin giving the best adsorption efficiency for orange peel pectin of 88,096% and banana peel pectin of 99,428%. From the isothermal analysis, the Langmuir and Freundlich isotherms can be applied to the adsorption of Fe metals using orange peel and banana peel pectin with a coefficient of determination of R2 ≥ 0.9.